2014
DOI: 10.1007/s12013-014-0167-2
|View full text |Cite
|
Sign up to set email alerts
|

Trans-arterial p53-Gene-Embolization with Gelatin Sponge Microparticles for Hepatocellular Carcinoma with BCLC Stage B: Single-Center Experience

Abstract: Trans-arterial chemoembolization for hepatic cellular carcinoma (HCC) is a recommended treatment schedule for stage B patients under the Barcelona-Clinic Liver Cancer (BCLC) diagnostic and treatment strategy system. Data from treatments with embolization performed with different embolizing microparticle reagents either alone or in combination with different chemotherapeutic agents showed favorable safety profile and significant efficacy in tumor control. In addition, recombinant adenoviral human p53 gene (rAd-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…In the current study, 4 cases succumbed to complications, such as tumor progression complicated with multiple organ failure, gastrointestinal bleeding and hepatic encephalopathy; however, patient mortality showed no direct correlation with GSM-TACE. The results of the present study were concordant with those of previous studies with regards to the safety and clinical efficacy of GSMs for the treatment of HCC (19)(20)(21). Pre-operative shock, low hemoglobin and albumin expression levels, prolonged prothrombin time, increased serum creatinine expression levels, hepatic encephalopathy, severe ascites, portal vein tumor thrombus and multinodular tumors in the left and right lobe are the primary factors that affect the treatment of HCC rupture hemorrhage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, 4 cases succumbed to complications, such as tumor progression complicated with multiple organ failure, gastrointestinal bleeding and hepatic encephalopathy; however, patient mortality showed no direct correlation with GSM-TACE. The results of the present study were concordant with those of previous studies with regards to the safety and clinical efficacy of GSMs for the treatment of HCC (19)(20)(21). Pre-operative shock, low hemoglobin and albumin expression levels, prolonged prothrombin time, increased serum creatinine expression levels, hepatic encephalopathy, severe ascites, portal vein tumor thrombus and multinodular tumors in the left and right lobe are the primary factors that affect the treatment of HCC rupture hemorrhage.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study using animal experimentation, performed at the Affiliated Zhongshan Hospital of Dalian University (Dalian, China), demonstrated the safety of GSMs (18). Clinical application studies have suggested that GSM-TACE in the treatment of HCC results in tumor necrosis and a reduction in tumor size, and has good clinical curative effects (19)(20)(21). The present study aimed to summarize the clinical hemostatic effect of GSM-TACE in the treatment of HCC, and to investigate the safety and efficacy of the clinical application of GSMs.…”
Section: Introductionmentioning
confidence: 99%
“…TACE procedures are currently widely used for various cases of HCC, mostly patients at BCLC stage B. Gelatin sponge microparticle (GSM) is an effective embolization agent, and a study reported that when compared with the ethiodized oil which is a permanent embolization agent, GSMs had many advantages, such as a higher tumor response rate at 1 month after treatment, especially in large tumors (13). Our previous clinical practices have confirmed the safety and efficacy of GSMs-TACE (5,14,15). It was found that 350-560 mm GSMs combined with single chemotherapy drug TACE procedures was effective and safe in treating elderly HCC without surgical resection, and more elderly patients may have better prognosis (5).…”
Section: Discussionmentioning
confidence: 87%
“…It was found that 350-560 mm GSMs combined with single chemotherapy drug TACE procedures was effective and safe in treating elderly HCC without surgical resection, and more elderly patients may have better prognosis (5). GSMs combined with trans-arterial p53-gene-embolization also achieved satisfactory efficacy in treating BCLC stage B HCC as evidenced by favorable survival rates (100% for both 6 and 12 months) and no significant complications (14). Therefore, GSMs were adopted in this study, and imaging scan confirmed the efficacy of GSMs-TACE.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment resulted in tumor necrosis and shrinking, rapid recovery of liver function, and good short-term effectiveness. [8] …”
Section: Introductionmentioning
confidence: 99%